(untitled) (International Journal of Engineering and Computer Science, 2017)
The image watermarking techniques are specially used to provide copyright protection, owners identification, image authentication and tamper detection. Water-marking technique is required to secure data and prevent unauthorized modification. The security and prevention from unauthorized modifications is due to rapid development of digital technologies, internet technologies and powerful image processing tools. Reversible watermarking becomes a promising technique to embed the information into important images. In this paper, we define the Region of Interest in an image and try to embed the data in Region of Non Interest. A basic idea of reversible watermarking is to select an embedding area in an image, embed the information into it and then rediscover the original image and information. If the amount of information need to embed is larger than embedding area, most of the techniques will consider lossless compression on the original values in the embedding area, and the space saved from compression will be used for embedding the watermark.